Quantitative description of co-assembly and evolution of small heat-shock proteins - Saman, D (2021)
Small heat-shock proteins (sHsps) are a family of molecular chaperones that are a part of the cellular proteostasis machinery. Many of them, such as human HspB1, HspB4 and HspB5 are polydisperse–they form a large range of stoichiometries. Some are also known to co-assemble, forming a large variety of sub-stoichiometries, with possible implications for their function.